THE PERCEPTION OF PARENTS AND INSTRUCTORS IN SWIMMING LESSONS FOR BABIES. (Fiep Bulletin - online, 2013)
Through this research, we tried to present the perception that the parents and instructors show regarding swimming lessons for babies at the moment of the transition of the baby who takes swimming lessons accompanied by the father or the mother, compared to lessons guided only by the company of the instructor. The importance of a good adaptation of the baby to the liquid environment is distinguished so that its transition is made with safety and pleasure. According to the literature, it is suggested to follow the use of a pedagogical process in order to develop the aquatic motor capacities, among them the sustentation, balance, propulsion of legs and arms, breath, fine motor coordination and fluctuation. A survey involving instructors and parents was carried out to detect the perception relating to the adaptation of the babies and we investigated whether the accuracy of the parents was similar to the one of the instructors.
Keywords: Adaptation; pedagogical process; motor capacity